Endoscopic Screening for Missed Lesions of Synchronous Multiple Early Gastric Cancer during Endoscopic Submucosal Dissection - Jiangnan Wan; Yi Fang; Haizhong Jiang; Bujiang Wang; Lei Xu; Chunjiu Hu; Honghui Chen; Xiaoyun Ding (Gastroenterology Research and Practice)
Aims. To evaluate the value of endoscopic screening during endoscopic submucosal dissection (ESD) in the detection of synchronous multiple early gastric cancer (SMEGC) and the risk factors for missed diagnosis of SMEGC. Methods. We conducted gastric endoscopic screening during ESD operation in 271 patients with early gastric cancer (EGC) referred for ESD, and endoscopic follow-up within 1 year after the operation. The detection and characteristics of SMEGC were analyzed in three stages: before ESD, during ESD operation, and within 1 year after ESD. Results. SMEGC was detected in 37 of 271 patients (13.6%). Among them, 21 patients with SMEGC (56.8%) were diagnosed before ESD, 9 (24.3%) were diagnosed with SMEGC by endoscopic screening during ESD operation, and 7 (18.9%) were found to have EGC lesions in the stomach during postoperative endoscopic follow-up within 1 year. The preoperative missed detection rate of SMEGC was 43.2%, and the rate of missed detection could be reduced by 24.3% (9/37) with endoscopic screening during ESD operation. Missed SMEGC lesions were more common in flat or depressed type and smaller in size than the lesions found before ESD. The presence of severe atrophic gastritis and age ≥60 years were significantly correlated with SMEGC (P<0.05), while multivariate analysis showed that age ≥60 years was an independent risk factor (OR = 2.63, P<0.05) for SMEGC. Conclusions. SMEGC lesions are apt to be missed endoscopically. Special attention should be paid to small, depressed, or flat lesions in detecting SMEGC, especially in elderly patients or (and) patients with severe atrophic gastritis. Endoscopic screening during ESD operation can effectively reduce the missed diagnosis rate of SMEGC.